Interleukin‐18 gene polymorphisms and risk of recurrent pregnancy loss: A systematic review and meta‐analysis. Issue 10 (8th September 2015) - Chen, Hui; Yang, Xiaorong; Du, Jinge; Lu, Ming
Abstract Interleukin‐18 (IL‐18) plays a potential pathological role in recurrent pregnancy loss (RPL). The results of published studies on the relationship between IL‐18 gene promoter polymorphisms (‐137G/C and‐607C/A) and RPL risk remain controversial. This meta‐analysis was performed to evaluate the association of IL‐18, ‐137G/C and‐607C/A gene polymorphisms with the risk of RPL under recessive, dominant and additive genetic models. A literature search was conducted in Medline, Embase and Web of Science for studies that described the effect of IL‐18 gene polymorphisms on RPL risk. The numbers of each ‐137G/C and‐607C/A genotype in the case and control groups were extracted. Quality of the original studies' methodology was also assessed. Meta‐analysis was performed using Stata 13.1 software and the fixed effect model was used. Five articles were included in this meta‐analysis. No significant heterogeneity between the studies was noted. The IL‐18 ‐137 G/C polymorphism was significantly associated with an increased risk of RPL under a recessive genetic model (CC vs. GG + CG: odds ratio = 1.56, 95% confidence interval = 1.13 2.15). For the ‐607C/A mutation, we failed to find any association under any genetic models. The Egger's regression asymmetry test showed no publication bias. Our present study indicates a positive association between the CC genotype of the IL‐18 ‐137G/C gene and RPL risk. Future well‐designed large studies are needed to validate the association between IL‐18 gene polymorphisms and the risk of RPL.